Peningkatan Pengetahuan mengenai Masalah Gizi pada Mahasiswa Indonesia dan Malaysia - Farah Nuriannisa; Ira Dwijayanti; Paramita Viantry; Merry Sunaryo; Sa'bania Hari Raharjeng; Dini Setiarsih; Nabila Al-Asdaq (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Nutritional issues among college students can impact various health problems, such as the risk of degenerative diseases, psychosocial issues, and academic performance. Indonesia and Malaysia are both developing countries facing the double burden of malnutrition. Prevention is required to combat the risk of double burden of malnutrition, such as education on nutritional issues. This activity aimed to enhance college students' knowledge about nutritional problems and their solutions, thereby improving students' quality of life and psychosocial well-being. The educational intervention involved 423 students from Indonesia and Malaysia. Based on evaluation, there was improvement in knowledge as much as 45.9% (pre-test 36.6 and post-test 53.4). This education activity was successfully improved students' knowledge about nutritional issues, thus the college students will improve their eating habits and lifestyles to avoid malnutrition.